A development of a damage monitoring system using an embedded fiber Bragg grating sensors - Hafizi, Z. M.; Nizwan, Che Ku Eddy; Ghazali, M. F.; Idris, Daing Mohamad Nafiz; Sani, M. S.M. (2019)
Glass-fibre reinforced polymer (GFRP) composite materials certainly have the undeniable favour over conventional metallic materials, notably in light weight to high strength ratio. However, these composite materials are prone to sudden catastrophic damage that requires the structural health monitoring (SHM). FBG sensor has shown a great potential in embedding and integrating with the composite materials, performing real-time monitoring of the structural condition. However, the main problems of FBG are the drawbacks in static and dynamic strain sensing monitoring assessment. Error in desired readings due to variations in output voltage and spectrum illustration for static strain interpretation are the drawbacks in static strain sensing. On the other hand, due to the presence of noise in the signal spectrum, the inaccuracy estimation of time of arrival (TOA) through peak detection are the drawback in dynamic strain sensing. Thus, the designation of this research study is to improve the current FBG based real-time monitoring system. Two specimens of composite plate and composite beam have been fabricated based on hand lay-up lamination method. FBG sensors are embedded in both the structures. For improvement in static strain measurement, the mesh-grid function utilized is capable of meshing the shapes of a structure, and display the deflection of the structure. The voltage normalization algorithm has reduced the output voltage variations from 26 data/minute to 17 data/minute with the elimination of pre-calibration each time before use. For the improvement in dynamic strain sensing, the merging of cross-correlation approach with linear source location technique (CC-LSL) has estimated the impact location close to the actual hit location with the largest relative error at only 2.47 %. From the conclusion of the study, it is truly believed that with this reputable sensing system, it is is one step closer to achieving the key concept of smart structure.